Inclusive Curriculum Education Modification Management (Case Study at Ponorogo National Immersion Primary School) - Umar Siddiq; Lailatul Istifadah (Al-Hayat Al-Istiqomah Foundation, 2018)
An inclusive school is a regular school that accommodates students with special needs, both those who have abnormalities or special talents that they all study in the same environment and place. One of the activities carried out is journal writing related to the implementation of learning in inclusive settings both done in regular class and Children's Stimulation Unit room. The Inclusive Culture program which was programmed at this institution was welcomed with positive support from parents, all elements of the school and the Education Office Government which are expected to have gradual changes in the inclusive school environment for the community and the District Education Office more aware of the importance of education for all.Sekolah inklusif merupakan sekolah regular yang mengakomodasi peserta didik dengan kebutuhan khusus, baik yang memiliki kelainan ataupun bakat istimewa yang mereka semua belajar dalam lingkungan dan tempat yang sama.Salah satu kegiatan yang dilakukan adalah ada penulisan jurnal terkait pelaksanaan pembelajaran dalam setting inklusif baik yang dilakukan di kelas reguler dan ruang Unit Stimulasi Anak. Program Inclusive Culture yang memang diprogramkan di lembaga ini disambut dengan dukungan positif dari orang tua murid, seluruh elemen sekolah dan Pemerintah Dinas Pendidikan yang diharapkan nantinya ada perubahan yang bertahap dalam lingkungan sekolah inklusif bagi masyarakat dan Dinas Pendidikan Kabupaten lebih sadar akan pentingnya pendidikan untuk semua.